2017
DOI: 10.1016/j.maturitas.2017.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Low vitamin D levels increase the risk of type 2 diabetes in older adults: A systematic review and meta-analysis

Abstract: .Low vitamin D levels increase the risk of type 2 diabetes in older adults: A systematic review and meta-analysis.Maturitas http://dx.doi.org/10.1016/j.maturitas. 2017.02.016 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 40 publications
4
40
1
10
Order By: Relevance
“…We found individuals with <30 nmol/L of serum 25(OH)D have ≈183% higher diabetes prevalence compared to those with ≥75 nmol/L 25(OH)D. This translates into 70% increased risk of having diabetes in those with <30 nmol/L serum 25(OH)D compared to those with ≥75 nmol/L serum 25(OH)D. In a recent meta-analysis based on 28,258 older subjects, Lucato et al [37] found that hypovitaminosis D was associated with incident diabetes (17%) at follow up after adjusting for confounding variables. The mechanism through which vitamin D modulates glucose homeostasis and the risk of diabetes is not clear.…”
Section: Discussionmentioning
confidence: 59%
“…We found individuals with <30 nmol/L of serum 25(OH)D have ≈183% higher diabetes prevalence compared to those with ≥75 nmol/L 25(OH)D. This translates into 70% increased risk of having diabetes in those with <30 nmol/L serum 25(OH)D compared to those with ≥75 nmol/L serum 25(OH)D. In a recent meta-analysis based on 28,258 older subjects, Lucato et al [37] found that hypovitaminosis D was associated with incident diabetes (17%) at follow up after adjusting for confounding variables. The mechanism through which vitamin D modulates glucose homeostasis and the risk of diabetes is not clear.…”
Section: Discussionmentioning
confidence: 59%
“…Clinical Severe cases associated with pneumonia Inverse correlation for CAP [68,69] Increased production of pro-inflammatory cytokines such as IL-6 Inverse correlation [70,71] Increased CRP Inverse correlation [72,73] Increased risk of sepsis Inverse correlation [74,75] Risk of ARDS Inverse correlation [76,77] Risk of heart failure Inverse correlation [78,79] Risk of diabetes mellitus Inverse correlation [67,80] Epidemiological Began in December 2019 in China, spread mainly to northern midlatitude countries Low 25(OH)D values in winter [48,81] Males have higher incidence and much higher CFRs than females Smoking reduces 25(OH)D [82] CFR increases with age Chronic disease rates increase with age; vitamin D plays a role in reducing risk of chronic diseases [83] Higher CFR for diabetics Diabetics may have lower 25(OH)D [84] Higher CFR for diabetics Lower 25(OH)D associated with increased risk of incidence [85] Higher CFR for hypertension Lower 25(OH)D may be associated with increased risk of incidence [86] Higher CFR for cardiovascular disease Lower 25(OH)D associated with increased risk of incidence and death [87] Higher CFR for chronic respiratory disease For COPD patients, 25(OH)D inversely correlated with risk, severity, and exacerbation [88] Found at higher rates in regions with elevated air pollution Air pollution associated with lower 25(OH)D concentrations [89] Note: 25-hydroxyvitamin D ((25(OH)D); acute respiratory distress syndrome (ARDS); community-acquired pneumonia (CAP); case-fatality rate (CFR); interleukin 6 (IL-6); chronic obstructive pulmonary disease (COPD); C-reactive protein (CRP); vitamin D deficiency (VDD). Table 3 lists some findings for vitamin D supplementation in reducing the clinical effects of COVID-19 infection found from treating other diseases.…”
Section: Characteristics Relation To 25(oh)d Referencementioning
confidence: 99%
“…Higher CFR for diabetics Lower 25(OH)D associated with increased risk of incidence [85] Higher CFR for hypertension Lower 25(OH)D may be associated with increased risk of incidence [86] Higher CFR for cardiovascular disease Lower 25(OH)D associated with increased risk of incidence and death [87] Higher CFR for chronic respiratory disease For COPD patients, 25(OH)D inversely correlated with risk, severity, and exacerbation [88] Found at higher rates in regions with elevated air pollution…”
Section: Clinical and Epidemiological Findings Regarding Covid-19mentioning
confidence: 99%